Solvent Concentration Effect on Powder X-Ray Diffraction And Dissolution Profiles Of Acyclovir-Nicotinamide Cocrystals - Dwi Setyawan (2017)
Objective : Acyclovir (ACV) is well-known antiviral agent that has absorption problem, mainly due to its poor solubility in water and oral bioavailability. To improve acyclovir physical properties, especially dissolution properties, acyclovir- nicotinamide(NCT) cocrystal was formed. Methods : ACV-NCT cocrystal was prepared using slurry method using ethanol as solvent with different concentration. The ACV-NCT cocrystal from each sample groups was characterized using powder X-ray diffraction (PXRD), and then dissolution properties evaluated. Results : Each ACV-NCT cocrystals prepared from slurry method with different ethanol concentrations have different PXRD profile. Dissolution analysis (ED 15 ) showed that ACV-NCT cocrystallization using slurry methods with 10,0 ml/g as ethanol concentration significantly increase ED 15 values compared to acyclovir and acyclovir-nicotinamide physical mixture (α=0,05). Conclusion : ACV-NCT cocrystal successfully formed using slurry method with 10,0 ml/g as optimal ethanol concentration.